Progress on performance assessment of ITER enhanced heat flux first wall technology after neutron irradiation. (1st February 2016) - Hirai, T; Bao, L; Barabash, V; Chappuis, Ph; Eaton, R; Escourbiac, F; Giqcuel, S; Merola, M; Mitteau, R; Raffray, R; Linke, J; Loewenhoff, Th; et al.
Abstract: ITER first wall (FW) panels are irradiated by energetic neutrons during the nuclear phase. Thus, an irradiation and high heat flux testing programme is undertaken by the ITER organization in order to evaluate the effects of neutron irradiation on the performance of enhanced heat flux (EHF) FW components. The test campaign includes neutron irradiation (up to 0.6–0.8 dpa at 200 °C–250 °C) of mock-ups that are representative of the final EHF FW panel design, followed by thermal fatigue tests (up to 4.7 MW m −2 ). Mock-ups were manufactured by the same manufacturing process as proposed for the series production. After a pre-irradiation thermal screening, eight mock-ups will be selected for the irradiation campaigns. This paper reports the preparatory work of HHF tests and neutron irradiation, assessment results as well as a brief description of mock-up manufacturing and inspection routes.